Ultra-high molecular weight polyethylene composite plastic and its application

By adding organically modified microcrystalline cellulose filler and carboxylated lignin fiber-hydrotalcite composite filler to ultra-high molecular weight polyethylene, the processing difficulties and insufficient performance caused by molecular chain entanglement are solved, and better fluidity, mechanical properties, heat resistance and flame retardancy are achieved.

CN118834459BActive Publication Date: 2025-04-15DONGGUAN AIZUNMEI PLASTIC ELECTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411001692.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2025-04-15
Estimated Expiration
2044-07-25

AI Technical Summary

Technical Problem

The molecular chain entanglement of ultra-high molecular weight polyethylene leads to low processing and molding quality and insufficient heat resistance and flame retardant properties, limiting its application range.

Method used

By adding organically modified microcrystalline cellulose filler and carboxylated lignin fiber-hydrotalcite composite filler to ultra-high molecular weight polyethylene, crystallization and detangling are promoted, fluidity and mechanical properties are improved, and heat resistance and flame retardant properties are enhanced through the stable combination of carboxylated lignin fibers and magnesium-aluminum hydrotalcite.

Benefits of technology

The flow performance, mechanical properties, heat resistance and flame retardant properties of ultra-high molecular weight polyethylene composite plastics have been significantly improved, and the processing and forming quality and efficiency have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118834459B_ABST
    Figure CN118834459B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of polymer materials, and more specifically, it relates to an ultra-high molecular weight polyethylene composite plastic and its application, wherein the ultra-high molecular weight polyethylene composite plastic comprises the following raw materials: ultra-high molecular weight polyethylene powder, organic modified microcrystalline cellulose filler, carboxylated lignin fiber-hydrotalcite composite filler, lubricant, compatibilizer and antioxidant. In the present invention, the organic modified microcrystalline cellulose filler is uniformly and dispersedly filled into the ultra-high molecular weight polyethylene matrix, which can enhance the mechanical properties of the ultra-high molecular weight polyethylene composite plastic; the carboxylated lignin fiber-hydrotalcite composite filler is filled into the ultra-high molecular weight polyethylene matrix, which not only makes the obtained ultra-high molecular weight polyethylene composite plastic have good heat resistance and flame retardant properties, but also helps to improve the flow properties of the ultra-high molecular weight polyethylene composite plastic in a molten state, and improves its processing quality and efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and more specifically, to an ultra-high molecular weight polyethylene composite plastic and its application. Background Art

[0002] Ultra-high molecular weight polyethylene generally refers to polyethylene with a relative molecular mass of more than 1.5 million. It has superior mechanical properties that other conventional molecular weight polyethylene do not have, such as impact resistance, wear resistance, chemical corrosion resistance, low temperature resistance, stress cracking resistance, anti-adhesion and self-lubrication.

[0003] Ultra-high molecular weight polyethylene has a high molecular weight, and its molecular chain is long and complex. In the molten state, the chain segments of ultra-high molecular weight polyethylene do not exist in parallel, but present a structural state similar to a "twisted" structure or an "8-shaped" structure. This structural feature causes the molecular chains of ultra-high molecular weight polyethylene to be easily entangled irregularly, forming many entanglement points. The existence of entanglement points will not only limit the movement and rearrangement of the molecular chains, resulting in high melt viscosity and poor fluidity, affecting the processing quality and efficiency of ultra-high molecular weight polyethylene, but also hinder the crystallization process, making it difficult for the molecular chains to reach an orderly crystallization state, thereby affecting the mechanical properties of ultra-high molecular weight polyethylene plastic after molding, and affecting the actual use quality of ultra-high molecular weight polyethylene.

[0004] Furthermore, as a thermoplastic, although ultra-high molecular weight polyethylene has excellent mechanical properties such as wear resistance and chemical corrosion resistance, its heat resistance and flame retardancy are not outstanding. As a result, although the heat resistance and dimensional stability of ultra-high molecular weight polyethylene are good under standard conditions, when encountering high temperature, temperature close to its melting point or flame, ultra-high molecular weight polyethylene may soften and deform, be easy to burn, produce molten droplets and other problems, which limits the application scope of ultra-high molecular weight polyethylene. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides an ultra-high molecular weight polyethylene composite material plastic and its application, which can disentangle the macromolecular chains of ultra-high molecular weight polyethylene, reduce the entanglement between the molecular chains of ultra-high molecular weight polyethylene, increase the flow properties of the ultra-high molecular weight polyethylene composite material plastic in a molten state, enhance the mechanical properties of the ultra-high molecular weight polyethylene composite material plastic, and make the ultra-high molecular weight polyethylene composite material plastic have good flame retardant properties and heat resistance.

[0006] An ultra-high molecular weight polyethylene composite plastic comprises the following raw materials:

[0007] 60-100 parts by weight of ultra-high molecular weight polyethylene powder, 10-30 parts by weight of organic modified microcrystalline cellulose filler, 8-24 parts by weight of carboxylated lignin fiber-hydrotalcite composite filler, 2-5 parts by weight of lubricant, 1-7 parts by weight of compatibilizer and 0.7-1.6 parts by weight of antioxidant;

[0008] The raw materials of the organic modified microcrystalline cellulose filler include: 25-40 parts by weight of acidified microcrystalline cellulose suspension and 25-60 parts by weight of KH-550 ethanol solution, wherein the KH-550 ethanol solution is prepared by mixing a silane coupling agent KH-550 and ethanol with a volume fraction of 95%, and the acidified microcrystalline cellulose suspension is prepared by dispersing microcrystalline cellulose in an ethanol solution with a volume fraction of 95%, and then acidifying and adjusting with acetic acid;

[0009] The raw materials of the carboxylated lignin fiber-hydrotalcite composite filler include: carboxylated lignin fiber and hydrotalcite dispersion, wherein the mass ratio of the carboxylated lignin fiber to the hydrotalcite dispersion is (1-6): (8-15), and the carboxylated lignin fiber is obtained by modifying the lignin fiber with glyoxylic acid;

[0010] The raw materials of the hydrotalcite dispersion include: magnesium aluminum hydrotalcite and a polyvinyl alcohol aqueous solution with a concentration of 0.8 g / L, and a solid-liquid mass ratio of (1-5):10.

[0011] Furthermore, the preparation method of the ultra-high molecular weight polyethylene composite plastic comprises the following steps:

[0012] S1: Surface modification of microcrystalline cellulose: adding an acidified microcrystalline cellulose suspension to a KH-550 ethanol solution and stirring for reaction; after the reaction is completed, centrifugation, precipitate collection, washing and vacuum drying are performed to obtain an organically modified microcrystalline cellulose filler;

[0013] S2: Carboxylation treatment of lignin fiber, adding lignin fiber to glyoxylic acid aqueous solution, stirring for reaction, then centrifugation, collecting filter residue, washing and vacuum drying to obtain carboxylated lignin fiber;

[0014] S3: Preparation of carboxylated lignin fiber-hydrotalcite composite filler, adding carboxylated lignin fiber to hydrotalcite dispersion, dispersing, filtering, washing, drying and grinding to obtain carboxylated lignin fiber-hydrotalcite composite filler;

[0015] S4: Preparation of ultra-high molecular weight polyethylene composite plastic, ultra-high molecular weight polyethylene powder, organic modified microcrystalline cellulose filler, carboxylated lignin fiber-hydrotalcite composite filler, lubricant, compatibilizer and antioxidant are mixed, and then melt-extruded, cooled and formed to obtain ultra-high molecular weight polyethylene composite plastic.

[0016] Furthermore, step S1 of surface modification of microcrystalline cellulose specifically comprises the following steps:

[0017] S1.1: 3 to 20 parts by weight of silane coupling agent KH-550 and 30 to 60 parts by weight of 95% ethanol solution are mixed evenly, and stirred and heated at 35 to 50° C. for 2 to 4 hours to obtain a KH-550 ethanol solution;

[0018] S1.2: adding 1 to 15 parts by weight of microcrystalline cellulose to 30 to 45 parts by weight of an ethanol solution having a volume fraction of 95%, and ultrasonically dispersing the solution for 5 to 10 minutes to obtain a microcrystalline cellulose suspension, and adding acetic acid to the microcrystalline cellulose suspension to adjust the pH value of the microcrystalline cellulose suspension to 4.0 to 4.5 to obtain an acidified microcrystalline cellulose suspension;

[0019] S1.3: Add 25-40 parts by weight of acidified microcrystalline cellulose suspension to 25-60 parts by weight of KH-550 ethanol solution, stir and react at 35-42°C for 2-4 hours. After the reaction is completed, centrifuge and separate the precipitate. Wash the precipitate 2-3 times with 75% by volume ethanol solution, and vacuum dry it at 50-60°C for 2-3 hours to obtain organically modified microcrystalline cellulose filler.

[0020] Furthermore, step S2, carboxylation treatment of lignin fiber, specifically comprises the following steps:

[0021] S2.1: adding lignin fiber to a glyoxylic acid aqueous solution with a concentration of 5 to 20 g / L, with a solid-liquid mass ratio of (1 to 10):20, stirring and reacting for 1 to 2 hours to obtain a mixed solution, adding a sodium bicarbonate solution to the mixed solution to adjust the pH value of the mixed solution to 6.0 to 6.5, and continuing to stir and react for 1 to 2 hours to obtain a reaction treatment mixed solution;

[0022] S2.2: Next, the reaction mixture is centrifuged to obtain a filter residue, which is washed 2 to 3 times with deionized water and then vacuum dried at 42 to 48° C. for 8 to 12 hours to obtain carboxylated lignin fibers.

[0023] Furthermore, step S3 of preparing the carboxylated lignin fiber-hydrotalcite composite filler specifically comprises the following steps:

[0024] S3.1: 20 to 40 parts by weight of magnesium nitrate, 30 to 50 parts by weight of aluminum nitrate and 200 to 350 parts by weight of deionized water are stirred and mixed, and after the solid is completely dissolved, a salt solution is obtained; 20 to 40 parts by weight of sodium hydroxide, 20 to 40 parts by weight of sodium carbonate and 150 to 300 parts by weight of deionized water are stirred and mixed, and after the solid is completely dissolved, an alkaline solution is obtained;

[0025] S3.2: The salt solution and the alkali solution are simultaneously added dropwise to the reactor in a volume ratio of 1: (1-1.5), the dropping speed of the salt solution and the alkali solution are both 1-3 drops / s, and the temperature is controlled at 60-70°C. After the salt solution and the alkali solution are added dropwise, stirring is continued for 30-50 minutes, and then aging is performed for 18-24 hours. After the aging is completed, the precipitate is filtered and collected, and the precipitate is washed, freeze-dried, ground, and passed through a 60-100 mesh sieve to obtain magnesium aluminum hydrotalcite;

[0026] S3.3: adding magnesium aluminum hydrotalcite to a polyvinyl alcohol aqueous solution with a concentration of 0.8 g / L, with a solid-liquid mass ratio of (1-5):10, and ultrasonically dispersing for 40-60 min to obtain a hydrotalcite dispersion;

[0027] S3.4: Add carboxylated lignin fiber to hydrotalcite dispersion, wherein the mass ratio of carboxylated lignin fiber to hydrotalcite dispersion is (1-6):(8-15), and ultrasonically disperse at 50-64°C for 1-3 hours, then stand and cool, and after cooling, filter, wash, dry and grind to obtain a carboxylated lignin fiber-hydrotalcite composite filler.

[0028] Furthermore, step S4 of preparing ultra-high molecular weight polyethylene composite plastic specifically comprises the following steps:

[0029] S4.1: 60 to 100 parts by weight of ultra-high molecular weight polyethylene powder, 10 to 30 parts by weight of organic modified microcrystalline cellulose filler, 8 to 24 parts by weight of carboxylated lignin fiber-hydrotalcite composite filler, 2 to 5 parts by weight of lubricant, 1 to 7 parts by weight of compatibilizer and 0.7 to 1.6 parts by weight of antioxidant are added to a high-speed mixer and mixed for 3 to 8 minutes to obtain a mixed material;

[0030] S4.2: adding the mixed material into a twin-screw extruder for melt extrusion at a temperature of 180-240°C;

[0031] S4.3: Cooling and shaping the extruded material to obtain an ultra-high molecular weight polyethylene composite plastic.

[0032] Furthermore, the main engine speed of the twin-screw extruder is 500-560rpm, the feeding speed is 25-35rpm, and the vacuum degree is ≤0.04MPa.

[0033] Furthermore, the molecular weight of the ultra-high molecular weight polyethylene powder is 3 to 6 million.

[0034] Furthermore, the compatibilizer is at least one of titanate coupling agent, silane coupling agent, aluminate coupling agent, monoethanolamine dodecyl sulfate, octadecylamine or isocyanate; the lubricant is at least one of polyethylene wax, calcium stearate or solid gypsum; and the antioxidant is at least one of phenolic antioxidant, phosphite antioxidant and vitamin E antioxidant.

[0035] The invention discloses an application of an ultra-high molecular weight polyethylene composite material plastic, wherein the ultra-high molecular weight polyethylene composite material plastic is used for preparing pipes, plates, rods or special-shaped materials.

[0036] The present invention has the following advantages:

[0037] 1. In the present invention, carboxylated lignin fibers are inserted into the lamellae of magnesium-aluminum hydrotalcite, and the carboxylated lignin fibers are fully and stably combined with the magnesium-aluminum hydrotalcite through intermolecular hydrogen bonds and electrostatic interactions. The obtained carboxylated lignin fiber-hydrotalcite composite filler is used as a filler and melt-extruded with ultra-high molecular weight polyethylene powder to obtain an ultra-high molecular weight polyethylene composite plastic, which not only has good heat resistance and flame retardant properties, but also the lamellae structure of the carboxylated lignin fiber-hydrotalcite composite filler can form a support between the ultra-high molecular weight polyethylene macromolecular chains, drive the ultra-high molecular weight polyethylene molecular chains to move, disentangle the ultra-high molecular weight polyethylene macromolecular chains, increase the flowability of the ultra-high molecular weight polyethylene composite plastic in a molten state, and then improve the mechanical properties of the ultra-high molecular weight polyethylene composite plastic, and improve its processing quality and efficiency.

[0038] 2. In the present invention, the organically modified microcrystalline cellulose filler is filled into the ultra-high molecular weight polyethylene matrix. The organically modified microcrystalline cellulose filler can act as a nucleating agent in the ultra-high molecular weight polyethylene matrix, promote crystallization through heterogeneous nucleation, reduce entanglement between ultra-high molecular weight polyethylene molecular chains, effectively regulate the movement and crystallinity of ultra-high molecular weight polyethylene molecular chains, and thus enhance the mechanical properties of ultra-high molecular weight polyethylene composite plastics.

[0039] 3. In the present invention, the silane coupling agent KH-550 is reacted with the hydroxyl groups on the surface of microcrystalline cellulose to carry out silanization reaction, thereby achieving organic modification of the surface of microcrystalline cellulose and improving the surface hydrophobicity of microcrystalline cellulose, thereby improving the compatibility of microcrystalline cellulose with an ultra-high molecular weight polyethylene matrix. The obtained organically modified microcrystalline cellulose filler can be uniformly dispersed in the ultra-high molecular weight polyethylene matrix, stably and effectively improving the mechanical properties of the ultra-high molecular weight polyethylene composite plastic, and avoiding agglomeration of microcrystalline cellulose in the ultra-high molecular weight polyethylene composite plastic. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1This is a scanning electron microscope (SEM) image of the ultra-high molecular weight polyethylene composite plastic prepared in Example 1.

[0041] Figure 2 The flowchart of the method for preparing ultra-high molecular weight polyethylene composite plastic in the embodiment of the present invention is shown in FIG. DETAILED DESCRIPTION

[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0043] A method for preparing an ultra-high molecular weight polyethylene composite plastic specifically comprises the following steps:

[0044] S1: Surface modification of microcrystalline cellulose,

[0045] S1.1: 20 parts by weight of silane coupling agent KH-550 and 60 parts by weight of 95% ethanol solution were mixed evenly, and the mixture was stirred and heated at 50° C. for 4 h to obtain a KH-550 ethanol solution;

[0046] S1.2: adding 15 parts by weight of microcrystalline cellulose to 45 parts by weight of 95% ethanol solution, and ultrasonically dispersing for 10 minutes to obtain a microcrystalline cellulose suspension, and adding acetic acid to the microcrystalline cellulose suspension to adjust the pH value of the microcrystalline cellulose suspension to 4.0 to obtain an acidified microcrystalline cellulose suspension;

[0047] S1.3: 40 parts by weight of the acidified microcrystalline cellulose suspension was added to 60 parts by weight of the KH-550 ethanol solution, and the mixture was stirred at 42°C for 4 hours. After the reaction was completed, the mixture was centrifuged to obtain a precipitate, which was washed three times with a 75% by volume ethanol solution, and then vacuum dried at 60°C for 3 hours to obtain an organically modified microcrystalline cellulose filler;

[0048] S2: Carboxylation of lignin fibers,

[0049] S2.1: adding lignin fiber to a 15 g / L glyoxylic acid aqueous solution at a solid-liquid mass ratio of 1:2, stirring and reacting for 2 h to obtain a mixed solution, adding sodium bicarbonate solution to the mixed solution to adjust the pH value of the mixed solution to 6.0, and continuing to stir and react for 2 h to obtain a reaction treatment mixed solution;

[0050] S2.2: Then, the reaction mixture is centrifuged to obtain a filter residue, which is washed three times with deionized water and then vacuum dried at 48° C. for 12 h to obtain carboxylated lignin fibers;

[0051] S3: Preparation of carboxylated lignin fiber-hydrotalcite composite filler,

[0052] S3.1: 40 parts by weight of magnesium nitrate, 50 parts by weight of aluminum nitrate and 350 parts by weight of deionized water are stirred and mixed, and after the solid is completely dissolved, a salt solution is obtained; 40 parts by weight of sodium hydroxide, 40 parts by weight of sodium carbonate and 300 parts by weight of deionized water are stirred and mixed, and after the solid is completely dissolved, an alkaline solution is obtained;

[0053] S3.2: The salt solution and the alkaline solution are simultaneously added dropwise to the reactor in a volume ratio of 1:1.5, the dropping speed of the salt solution and the alkaline solution are both 3 drops / s, and the temperature is controlled at 70°C. After the salt solution and the alkaline solution are added dropwise, stirring is continued for 50 minutes, and then aging is carried out for 24 hours. After the aging is completed, the precipitate is filtered and collected, and the precipitate is washed, freeze-dried, ground, and passed through a 100-mesh sieve to obtain magnesium aluminum hydrotalcite;

[0054] S3.3: adding magnesium aluminum hydrotalcite to a polyvinyl alcohol aqueous solution with a concentration of 0.8 g / L, with a solid-liquid mass ratio of 1:2, and ultrasonically dispersing for 60 min to obtain a hydrotalcite dispersion;

[0055] S3.4: adding carboxylated lignin fiber to the hydrotalcite dispersion, wherein the mass ratio of carboxylated lignin fiber to hydrotalcite dispersion is 2:5, and ultrasonically dispersing at 64°C for 3 hours, then standing to cool, and after cooling, filtering, washing, drying and grinding to obtain a carboxylated lignin fiber-hydrotalcite composite filler;

[0056] S4: Preparation of ultra-high molecular weight polyethylene composite plastics,

[0057] S4.1: 100 parts by weight of ultra-high molecular weight polyethylene powder, 30 parts by weight of organic modified microcrystalline cellulose filler, 24 parts by weight of carboxylated lignin fiber-hydrotalcite composite filler, 5 parts by weight of calcium stearate, 7 parts by weight of octadecylamine and 1.6 parts by weight of antioxidant 1010 are added to a high-speed mixer and mixed for 8 minutes to obtain a mixed material;

[0058] S4.2: Add the mixed material into a twin-screw extruder for melt extrusion, the extrusion temperature is 240°C, the main engine speed of the twin-screw extruder is 560rpm, the feed speed is 35rpm, and the vacuum degree is 0.04MPa;

[0059] S4.3: Cooling and shaping the extruded material to obtain an ultra-high molecular weight polyethylene composite plastic. Figure 1 This is a scanning electron microscope image of ultra-high molecular weight polyethylene composite plastic. Example 2

[0060] A method for preparing an ultra-high molecular weight polyethylene composite plastic specifically comprises the following steps:

[0061] S1: Surface modification of microcrystalline cellulose,

[0062] S1.1: 20 parts by weight of silane coupling agent KH-550 and 60 parts by weight of 95% ethanol solution were mixed evenly, and the mixture was stirred and heated at 35°C for 2 hours to obtain a KH-550 ethanol solution;

[0063] S1.2: adding 15 parts by weight of microcrystalline cellulose to 45 parts by weight of 95% ethanol solution, and ultrasonically dispersing for 5 minutes to obtain a microcrystalline cellulose suspension, and adding acetic acid to the microcrystalline cellulose suspension to adjust the pH value of the microcrystalline cellulose suspension to 4.5 to obtain an acidified microcrystalline cellulose suspension;

[0064] S1.3: 40 parts by weight of the acidified microcrystalline cellulose suspension was added to 60 parts by weight of the KH-550 ethanol solution, and the mixture was stirred at 35°C for 2 hours. After the reaction was completed, the mixture was centrifuged to obtain a precipitate, which was washed twice with a 75% by volume ethanol solution, and then vacuum dried at 50°C for 2 hours to obtain an organically modified microcrystalline cellulose filler;

[0065] S2: Carboxylation of lignin fibers,

[0066] S2.1: adding lignin fiber to a 15 g / L glyoxylic acid aqueous solution at a solid-liquid mass ratio of 1:2, stirring and reacting for 1 hour to obtain a mixed solution, adding sodium bicarbonate solution to the mixed solution to adjust the pH value of the mixed solution to 6.5, and continuing to stir and react for 1 hour to obtain a reaction treatment mixed solution;

[0067] S2.2: Then, the reaction mixture is centrifuged to obtain a filter residue, which is washed twice with deionized water and then vacuum dried at 42° C. for 8 h to obtain carboxylated lignin fibers;

[0068] S3: Preparation of carboxylated lignin fiber-hydrotalcite composite filler,

[0069] S3.1: 40 parts by weight of magnesium nitrate, 50 parts by weight of aluminum nitrate and 350 parts by weight of deionized water are stirred and mixed, and after the solid is completely dissolved, a salt solution is obtained; 40 parts by weight of sodium hydroxide, 40 parts by weight of sodium carbonate and 300 parts by weight of deionized water are stirred and mixed, and after the solid is completely dissolved, an alkaline solution is obtained;

[0070] S3.2: The salt solution and the alkaline solution are simultaneously added dropwise to the reactor in a volume ratio of 1:1.5, the dropping speed of the salt solution and the alkaline solution are both 1 drop / s, and the temperature is controlled at 60°C. After the salt solution and the alkaline solution are added dropwise, stirring is continued for 30 minutes, and then aging is performed for 18 hours. After the aging is completed, the precipitate is filtered and collected, and the precipitate is washed, freeze-dried, ground, and passed through a 100-mesh sieve to obtain magnesium aluminum hydrotalcite;

[0071] S3.3: adding magnesium aluminum hydrotalcite to a polyvinyl alcohol aqueous solution with a concentration of 0.8 g / L, with a solid-liquid mass ratio of 1:2, and ultrasonically dispersing for 40 minutes to obtain a hydrotalcite dispersion;

[0072] S3.4: adding carboxylated lignin fiber to the hydrotalcite dispersion, wherein the mass ratio of carboxylated lignin fiber to the hydrotalcite dispersion is 2:5, and ultrasonically dispersing at 50°C for 1 hour, then standing to cool, and after cooling, filtering, washing, drying and grinding to obtain a carboxylated lignin fiber-hydrotalcite composite filler;

[0073] S4: Preparation of ultra-high molecular weight polyethylene composite plastics,

[0074] S4.1: 100 parts by weight of ultra-high molecular weight polyethylene powder, 30 parts by weight of organic modified microcrystalline cellulose filler, 24 parts by weight of carboxylated lignin fiber-hydrotalcite composite filler, 5 parts by weight of polyethylene wax, 7 parts by weight of silane coupling agent KH-570 and 1.6 parts by weight of antioxidant 1076 are added to a high-speed mixer and mixed for 8 minutes to obtain a mixed material;

[0075] S4.2: Add the mixed material into a twin-screw extruder for melt extrusion, the extrusion temperature is 240°C, the main engine speed of the twin-screw extruder is 560rpm, the feed speed is 35rpm, and the vacuum degree is 0.04MPa;

[0076] S4.3: Cooling and shaping the extruded material to obtain an ultra-high molecular weight polyethylene composite plastic. Example 3

[0077] A method for preparing an ultra-high molecular weight polyethylene composite plastic specifically comprises the following steps:

[0078] S1: Surface modification of microcrystalline cellulose,

[0079] S1.1: 5 parts by weight of silane coupling agent KH-550 and 30 parts by weight of 95% ethanol solution were mixed evenly, and stirred and heated at 50° C. for 4 hours to obtain a KH-550 ethanol solution;

[0080] S1.2: adding 5 parts by weight of microcrystalline cellulose to 30 parts by weight of 95% ethanol solution, and ultrasonically dispersing for 10 minutes to obtain a microcrystalline cellulose suspension, and adding acetic acid to the microcrystalline cellulose suspension to adjust the pH value of the microcrystalline cellulose suspension to 4.0 to obtain an acidified microcrystalline cellulose suspension;

[0081] S1.3: Add 25 parts by weight of the acidified microcrystalline cellulose suspension to 25 parts by weight of the KH-550 ethanol solution, stir and react at 42°C for 4 hours, centrifuge and separate the precipitate after the reaction is completed, wash the precipitate three times with a 75% by volume ethanol solution, and vacuum dry it at 60°C for 3 hours to obtain an organically modified microcrystalline cellulose filler;

[0082] S2: Carboxylation of lignin fibers,

[0083] S2.1: adding lignin fiber to a 15 g / L glyoxylic acid aqueous solution at a solid-liquid mass ratio of 1:4, stirring and reacting for 2 h to obtain a mixed solution, adding sodium bicarbonate solution to the mixed solution to adjust the pH value of the mixed solution to 6.0, and continuing to stir and react for 2 h to obtain a reaction treatment mixed solution;

[0084] S2.2: Then, the reaction mixture is centrifuged to obtain a filter residue, which is washed three times with deionized water and then vacuum dried at 48° C. for 8 h to obtain carboxylated lignin fibers;

[0085] S3: Preparation of carboxylated lignin fiber-hydrotalcite composite filler,

[0086] S3.1: 20 parts by weight of magnesium nitrate, 30 parts by weight of aluminum nitrate and 200 parts by weight of deionized water are stirred and mixed, and after the solid is completely dissolved, a salt solution is obtained; 20 parts by weight of sodium hydroxide, 20 parts by weight of sodium carbonate and 150 parts by weight of deionized water are stirred and mixed, and after the solid is completely dissolved, an alkaline solution is obtained;

[0087] S3.2: The salt solution and the alkaline solution are simultaneously added dropwise to the reactor in a volume ratio of 1:1, and the dropping speed of the salt solution and the alkaline solution is 3 drops / s. Stirring is performed while dropping, and the temperature is controlled at 70°C. After the salt solution and the alkaline solution are added dropwise, stirring is continued for 50 minutes, and then aging is performed for 24 hours. After the aging is completed, the precipitate is filtered and collected. After washing, freeze-drying, grinding, and passing through a 100-mesh sieve, magnesium-aluminum hydrotalcite is obtained;

[0088] S3.3: adding magnesium aluminum hydrotalcite to a polyvinyl alcohol aqueous solution with a concentration of 0.8 g / L, with a solid-liquid mass ratio of 1:10, and ultrasonically dispersing for 60 min to obtain a hydrotalcite dispersion;

[0089] S3.4: adding carboxylated lignin fiber to the hydrotalcite dispersion, wherein the mass ratio of carboxylated lignin fiber to hydrotalcite dispersion is 1:8, and ultrasonically dispersing at 64°C for 3 hours, then standing to cool, and after cooling, filtering, washing, drying and grinding to obtain a carboxylated lignin fiber-hydrotalcite composite filler;

[0090] S4: Preparation of ultra-high molecular weight polyethylene composite plastics,

[0091] S4.1: 60 parts by weight of ultra-high molecular weight polyethylene powder, 10 parts by weight of organic modified microcrystalline cellulose filler, 10 parts by weight of carboxylated lignin fiber-hydrotalcite composite filler, 2 parts by weight of calcium stearate, 1 part by weight of octadecylamine and 0.7 parts by weight of antioxidant 1010 were added to a high-speed mixer and mixed for 8 minutes to obtain a mixed material;

[0092] S4.2: Add the mixed material into a twin-screw extruder for melt extrusion, the extrusion temperature is 240°C, the main engine speed of the twin-screw extruder is 560rpm, the feed speed is 35rpm, and the vacuum degree is 0.04MPa;

[0093] S4.3: Cooling and shaping the extruded material to obtain an ultra-high molecular weight polyethylene composite plastic.

[0094] Comparative Example 1

[0095] Compared with Example 1, the difference of Comparative Example 1 is that the carboxylated lignin fiber-hydrotalcite composite filler in step S4.1 is removed, and the other steps remain unchanged to prepare an ultra-high molecular weight polyethylene composite plastic, which is recorded as Comparative Example 1.

[0096] Comparative Example 2

[0097] Compared with Example 1, the difference of Comparative Example 2 is that the carboxylated lignin fiber-hydrotalcite composite filler in step S4.1 is replaced with an equal weight portion of magnesium aluminum hydrotalcite, and the other steps remain unchanged to prepare an ultra-high molecular weight polyethylene composite plastic, which is recorded as Comparative Example 2.

[0098] Comparative Example 3

[0099] Compared with Example 1, the difference of Comparative Example 3 is that the carboxylated lignin fiber-hydrotalcite composite filler in step S4.1 is replaced with an equal weight portion of carboxylated lignin fiber, and the other steps remain unchanged to prepare an ultra-high molecular weight polyethylene composite plastic, which is recorded as Comparative Example 3.

[0100] Comparative Example 4

[0101] Compared with Example 1, the difference of Comparative Example 4 is that the organically modified microcrystalline cellulose filler in step S4.1 is removed, and the other steps remain unchanged to prepare an ultra-high molecular weight polyethylene composite plastic, which is recorded as Comparative Example 4.

[0102] Comparative Example 5

[0103] Compared with Example 1, the difference of Comparative Example 5 is that the organically modified microcrystalline cellulose filler in step S4.1 is replaced with microcrystalline cellulose of equal weight, and the other steps remain unchanged to prepare an ultra-high molecular weight polyethylene composite plastic, which is recorded as Comparative Example 5.

[0104] Performance Testing

[0105] The ultra-high molecular weight polyethylene composite plastic obtained in Examples 1-3 and Comparative Examples 1-3 was tested for heat resistance according to the standard of GB / T1634-2004; the ultra-high molecular weight polyethylene composite plastic obtained in Examples 1-3 and Comparative Examples 1-3 was tested for flame retardancy according to the standard of GB / T2406.2-2009; the ultra-high molecular weight polyethylene composite plastic obtained in Examples 1-3 and Comparative Examples 1-3 was tested for melt flowability according to the standard of GB / T3682-2018. The results are shown in Table 1.

[0106]

[0107] As can be seen from Table 1, the test results of heat deformation temperature, oxygen index and melt index of the ultra-high molecular weight polyethylene composite plastic prepared in Examples 1-3 are all greater than those of the ultra-high molecular weight polyethylene composite plastic prepared in Comparative Example 1, indicating that the addition of carboxylated lignin fiber-hydrotalcite composite filler can effectively improve the heat resistance and flame retardancy of the ultra-high molecular weight polyethylene composite plastic, and promote the flow properties of the ultra-high molecular weight polyethylene composite plastic in a molten state. Furthermore, compared with Comparative Examples 2-3 in which only carboxylated lignin fiber or magnesium-aluminum hydrotalcite was added, the test results of thermal deformation temperature, oxygen index and melt index of the ultra-high molecular weight polyethylene composite plastic obtained by using carboxylated lignin fiber-hydrotalcite composite filler as filler in Examples 1-3 were better, indicating that the carboxylated lignin fiber and magnesium-aluminum hydrotalcite in the carboxylated lignin fiber-hydrotalcite composite filler had a synergistic promoting effect, and after the carboxylated lignin fiber and magnesium-aluminum hydrotalcite were stably combined with each other, the heat resistance, flame retardancy and melt flow properties of the ultra-high molecular weight polyethylene composite plastic could be more significantly improved.

[0108] The ultra-high molecular weight polyethylene composite plastics obtained in Examples 1-3 and Comparative Examples 1-5 were subjected to a tensile strength test according to the standard of GB / T1040.1-2018; the ultra-high molecular weight polyethylene composite plastics obtained in Examples 1-5 and Comparative Examples 1-3 were subjected to a bending strength test according to the standard of GB / T9341-2008; the ultra-high molecular weight polyethylene composite plastics obtained in Examples 1-3 and Comparative Examples 1-5 were subjected to an impact strength test according to the standard of GB / T1043.1-2016. The results are shown in Table 2.

[0109]

[0110] As shown in Table 2, the test results of the above-mentioned mechanical properties of the ultra-high molecular weight polyethylene composite plastic prepared in Examples 1-3 are better than those of the ultra-high molecular weight polyethylene composite plastic prepared in Comparative Examples 1-5, indicating that the addition of carboxylated lignin fiber-hydrotalcite composite filler and organic modified microcrystalline cellulose filler can effectively improve the mechanical properties of the ultra-high molecular weight polyethylene composite plastic, and the role played by the organic modified microcrystalline cellulose filler is more significant. Furthermore, it can be seen from the results of Examples 1-3 and Comparative Example 5 that, compared with the direct addition of untreated microcrystalline cellulose, the organic modified microcrystalline cellulose filler has a more significant effect on improving the mechanical properties of the ultra-high molecular weight polyethylene composite plastic.

[0111] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all such improvements and changes should fall within the scope of protection of the appended claims of the present invention. Parts not described in detail in this specification belong to the prior art known to those skilled in the art.

Claims

1. An ultra-high molecular weight polyethylene composite plastic, characterized in that: Including the following raw materials: 60-100 parts by weight of ultra-high molecular weight polyethylene powder, 10-30 parts by weight of organic modified microcrystalline cellulose filler, 8-24 parts by weight of carboxylated lignin fiber-hydrotalcite composite filler, 2-5 parts by weight of lubricant, 1-7 parts by weight of compatibilizer and 0.7-1.6 parts by weight of antioxidant; The raw materials of the organic modified microcrystalline cellulose filler include: 25-40 parts by weight of acidified microcrystalline cellulose suspension and 25-60 parts by weight of KH-550 ethanol solution, wherein the KH-550 ethanol solution is prepared by mixing a silane coupling agent KH-550 and ethanol with a volume fraction of 95%, and the acidified microcrystalline cellulose suspension is prepared by dispersing microcrystalline cellulose in an ethanol solution with a volume fraction of 95%, and then acidifying and adjusting with acetic acid; The raw materials of the carboxylated lignin fiber-hydrotalcite composite filler include: carboxylated lignin fiber and hydrotalcite dispersion, wherein the mass ratio of the carboxylated lignin fiber to the hydrotalcite dispersion is (1-6): (8-15), and the carboxylated lignin fiber is obtained by modifying the lignin fiber with glyoxylic acid; The raw materials of the hydrotalcite dispersion include: magnesium aluminum hydrotalcite and a polyvinyl alcohol aqueous solution with a concentration of 0.8 g / L, and a solid-liquid mass ratio of (1-5):10; The preparation method of ultra-high molecular weight polyethylene composite plastic comprises the following steps: S1: Surface modification of microcrystalline cellulose: adding an acidified microcrystalline cellulose suspension to a KH-550 ethanol solution and stirring for reaction; after the reaction is completed, centrifugation, precipitate collection, washing and vacuum drying are performed to obtain an organically modified microcrystalline cellulose filler; S2: Carboxylation treatment of lignin fiber, adding lignin fiber to glyoxylic acid aqueous solution, stirring for reaction, then centrifugation, collecting filter residue, washing and vacuum drying to obtain carboxylated lignin fiber; S3: Preparation of carboxylated lignin fiber-hydrotalcite composite filler, adding carboxylated lignin fiber to hydrotalcite dispersion, dispersing, filtering, washing, drying and grinding to obtain carboxylated lignin fiber-hydrotalcite composite filler; S4: Preparation of ultra-high molecular weight polyethylene composite plastic, ultra-high molecular weight polyethylene powder, organic modified microcrystalline cellulose filler, carboxylated lignin fiber-hydrotalcite composite filler, lubricant, compatibilizer and antioxidant are mixed, and then melt-extruded, cooled and formed to obtain ultra-high molecular weight polyethylene composite plastic.

2. The ultra-high molecular weight polyethylene composite plastic according to claim 1, characterized in that: Step S1: surface modification of microcrystalline cellulose, specifically comprising the following steps: S1.1: 3 to 20 parts by weight of silane coupling agent KH-550 and 30 to 60 parts by weight of 95% ethanol solution are mixed evenly, and stirred and heated at 35 to 50° C. for 2 to 4 hours to obtain a KH-550 ethanol solution; S1.2: adding 1 to 15 parts by weight of microcrystalline cellulose to 30 to 45 parts by weight of an ethanol solution having a volume fraction of 95%, and ultrasonically dispersing the solution for 5 to 10 minutes to obtain a microcrystalline cellulose suspension, and adding acetic acid to the microcrystalline cellulose suspension to adjust the pH value of the microcrystalline cellulose suspension to 4.0 to 4.5 to obtain an acidified microcrystalline cellulose suspension; S1.3: Add 25-40 parts by weight of acidified microcrystalline cellulose suspension to 25-60 parts by weight of KH-550 ethanol solution, stir and react at 35-42°C for 2-4 hours. After the reaction is completed, centrifuge and separate the precipitate. Wash the precipitate 2-3 times with 75% by volume ethanol solution, and vacuum dry it at 50-60°C for 2-3 hours to obtain organically modified microcrystalline cellulose filler.

3. The ultra-high molecular weight polyethylene composite plastic according to claim 2, characterized in that: Step S2: carboxylation treatment of lignin fiber, specifically comprising the following steps: S2.1: adding lignin fiber to a glyoxylic acid aqueous solution with a concentration of 5 to 20 g / L, with a solid-liquid mass ratio of (1 to 10):20, stirring and reacting for 1 to 2 hours to obtain a mixed solution, adding a sodium bicarbonate solution to the mixed solution to adjust the pH value of the mixed solution to 6.0 to 6.5, and continuing to stir and react for 1 to 2 hours to obtain a reaction treatment mixed solution; S2.2: Next, the reaction mixture is centrifuged to obtain a filter residue, which is washed 2 to 3 times with deionized water and then vacuum dried at 42 to 48° C. for 8 to 12 hours to obtain carboxylated lignin fibers.

4. The ultra-high molecular weight polyethylene composite plastic according to claim 3, characterized in that: Step S3 is to prepare the carboxylated lignin fiber-hydrotalcite composite filler, which specifically comprises the following steps: S3.1: 20 to 40 parts by weight of magnesium nitrate, 30 to 50 parts by weight of aluminum nitrate and 200 to 350 parts by weight of deionized water are stirred and mixed, and after the solid is completely dissolved, a salt solution is obtained; 20 to 40 parts by weight of sodium hydroxide, 20 to 40 parts by weight of sodium carbonate and 150 to 300 parts by weight of deionized water are stirred and mixed, and after the solid is completely dissolved, an alkaline solution is obtained; S3.2: The salt solution and the alkali solution are simultaneously added dropwise to the reactor in a volume ratio of 1: (1-1.5), the dropping speed of the salt solution and the alkali solution are both 1-3 drops / s, and the temperature is controlled at 60-70°C. After the salt solution and the alkali solution are added dropwise, stirring is continued for 30-50 minutes, and then aging is performed for 18-24 hours. After the aging is completed, the precipitate is filtered and collected, and the precipitate is washed, freeze-dried, ground, and passed through a 60-100 mesh sieve to obtain magnesium aluminum hydrotalcite; S3.3: adding magnesium aluminum hydrotalcite to a polyvinyl alcohol aqueous solution with a concentration of 0.8 g / L, with a solid-liquid mass ratio of (1-5):10, and ultrasonically dispersing for 40-60 min to obtain a hydrotalcite dispersion; S3.4: Add carboxylated lignin fiber to hydrotalcite dispersion, wherein the mass ratio of carboxylated lignin fiber to hydrotalcite dispersion is (1-6):(8-15), and ultrasonically disperse at 50-64°C for 1-3 hours, then stand and cool, and after cooling, filter, wash, dry and grind to obtain a carboxylated lignin fiber-hydrotalcite composite filler.

5. The ultra-high molecular weight polyethylene composite plastic according to claim 4, characterized in that: Step S4: preparing ultra-high molecular weight polyethylene composite plastic, specifically comprising the following steps: S4.1: 60 to 100 parts by weight of ultra-high molecular weight polyethylene powder, 10 to 30 parts by weight of organic modified microcrystalline cellulose filler, 8 to 24 parts by weight of carboxylated lignin fiber-hydrotalcite composite filler, 2 to 5 parts by weight of lubricant, 1 to 7 parts by weight of compatibilizer and 0.7 to 1.6 parts by weight of antioxidant are added to a high-speed mixer and mixed for 3 to 8 minutes to obtain a mixed material; S4.2: adding the mixed material into a twin-screw extruder for melt extrusion at a temperature of 180-240°C; S4.3: Cooling and shaping the extruded material to obtain an ultra-high molecular weight polyethylene composite plastic.

6. The ultra-high molecular weight polyethylene composite plastic according to claim 5, characterized in that: The main engine speed of the twin-screw extruder is 500-560rpm, the feeding speed is 25-35rpm, and the vacuum degree is ≤0.04MPa.

7. The ultra-high molecular weight polyethylene composite plastic according to claim 1, characterized in that: The molecular weight of ultra-high molecular weight polyethylene powder is 3 to 6 million.

8. The ultra-high molecular weight polyethylene composite plastic according to claim 1, characterized in that: The compatibilizer is at least one of titanate coupling agent, silane coupling agent, aluminate coupling agent, monoethanolamine dodecyl sulfate, octadecylamine or isocyanate; the lubricant is at least one of polyethylene wax, calcium stearate or solid gypsum; the antioxidant is at least one of phenolic antioxidant, phosphite antioxidant and vitamin E antioxidant.

9. The use of the ultra-high molecular weight polyethylene composite plastic according to any one of claims 1 to 8, characterized in that: Ultra-high molecular weight polyethylene composite plastics are used to make pipes, plates, rods or profiles.

Citation Information

Patent Citations

  • Preparation method for polyolefin material with high strength, no halogen and flame retardancy

    CN108047527A

  • Antibacterial and deodorizing plastic for garbage cans and preparation method thereof

    CN111978614A